Alexandra Kollontai : the lonely struggle of the woman who defied Lenin - Porter, Cathy (New York : Dial Press, 1980)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Kollontaj, Aleksandra Michajlovna; Russische revolutie; Sovjet-Unie.